Developmental competence of domestic cat vitrified oocytes in 3D enriched culture conditions - Colombo, Martina; Morselli, Maria Giorgia; Tavares, Mariana Riboli [UNESP]; Apparicio, Maricy [UNESP]; Luvoni, Gaia Cecilia (MDPI, 2019)
Cryoinjuries severely affect the competence of vitrified oocytes (VOs) to develop into embryos after warming. The use of culture conditions that provide physical and chemical support and resemble the in vivo microenvironment in which oocytes develop, such as 3D scaffolds and coculture systems, might be useful to improve VOs outcomes. In this study, an enriched culture system of 3D barium alginate microcapsules was employed for the in vitro embryo production of domestic cat VOs. Cryotop vitrified-warmed oocytes were in vitro matured for 24 h in the 3D system with or without fresh cumulus-oocyte complexes (COCs) in coculture, whereas a control group of VOs was cultured in traditional 2D microdrops of medium. After in vitro fertilization, presumptive embryos were cultured in 3D or 2D systems according to the maturation conditions. Vitrified oocytes were able to mature and develop into embryos in 3D microcapsules (17.42 ± 11.83%) as well as in 2D microdrops (14.96 ± 8.80%), but the coculture with companion COCs in 3D resulted in similar proportions of VOs embryo development (18.39 ± 16.67%; p = 1.00), although COCs presence allowed for blastocyst formation (0.95 ± 2.52%). In conclusion, embryos until late developmental stages were obtained from cat VOs, and 3D microcapsules were comparable to 2D microdrops, but improvements in post-warming conditions are still needed.
Keywords: Alginate microcapsule; Blastocyst; Cryopreservation; Feline; In vitro culture; Three-dimensional